Stent-assisted coiling of hepatic artery pseudoaneurysm in a liver transplant recipient - Shubham Suryavanshi; Akhil Baby; Sudheer Pargewar; Rochan Pant; Rajesh Sasidharan (Egyptian Liver Journal)
Abstract Background Hepatic artery pseudoaneurysms (HAP) are rare but life-threatening vascular complications that can occur after hepatobiliary or pancreatic surgeries, particularly in liver transplant recipients. The iatrogenic nature of these lesions often stems from surgical trauma, electrocautery injury, or postoperative interventions. Clinical presentation varies from gastrointestinal bleeding to hemobilia or abdominal pain. Endovascular therapy is the preferred treatment modality, especially in patients with altered anatomy and compromised hepatic collateral circulation. In liver transplant recipients, preservation of the hepatic artery is crucial, as it provides the sole arterial supply to the allograft biliary system. Traditional embolization methods risk hepatic infarction or biliary ischemia in this context. While covered stents offer a solution by preserving flow, their deployment can be technically challenging due to vascular tortuosity. Stent-assisted coiling emerges as a viable alternative for excluding pseudoaneurysms (PSAs) while maintaining parent artery patency. Case presentation We report a case of a 45-year-old male with metabolic dysfunction-associated steatotic liver disease who underwent living donor liver transplantation using a right lobe graft. One year post-transplant, he developed a biliary anastomotic stricture, necessitating hepaticojejunostomy. One week postoperatively, he presented with melena and significant hemoglobin drop. CT angiography revealed a wide-necked intrahepatic pseudoaneurysm arising from the anterior branch of the right hepatic artery. An endovascular approach was employed with the goal of preserving hepatic perfusion. Using femoral arterial access, the lesion was crossed with a balloon-mounted stent, which was deployed across the PSA neck. A microcatheter was then navigated into the aneurysmal sac, and five detachable microcoils were delivered. Completion angiography confirmed complete exclusion of the PSA with preserved flow through the hepatic artery. The patient had no recurrent bleeding, with imaging at follow-up confirming stent patency and clinical stability at 9 months. Conclusion Stent-assisted coiling offers a safe and effective solution for managing wide-necked HAPs in post-transplant patients, especially when parent artery preservation is essential. This technique avoids the ischemic complications associated with embolization and circumvents the technical limitations of covered stent placement in tortuous vasculature. It should be considered a frontline option in anatomically challenging hepatic PSA cases post liver transplantation.